2016
DOI: 10.1021/acs.jpcc.6b05692
|View full text |Cite
|
Sign up to set email alerts
|

Standard and Fast Selective Catalytic Reduction of NO with NH3 on Zeolites Fe-BEA

Abstract: International audienceTwo Fe-containing BEA zeolites were prepared by ion-exchange (IE; Fe-BEA) and postsynthesis (PS; Fe-BEA/DeAl) procedures. Similar Fe content (0.8 to 0.9 Fe wt%) was evidenced for studied samples. Fe-BEA, prepared by ion exchange, contained essentially iron cations at the exchange sites of the zeolite. These iron cations are either isolated or bridged through an oxygen atom (Fe-oxo cations). In Fe-BEA/DeAl, a high portion of iron was introduced in the T-positions of zeolite lattice. The ot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 81 publications
0
18
0
Order By: Relevance
“…However, the main drawback of V 2 O 5 -WO 3 (MoO 3 )/TiO 2 is a narrow operating temperature window (300-400 • C), sublimation of vanadium species at high temperatures, and high oxidation of SO 2 to SO 3 leading to a decrease of NOx conversion at 400 • C [10]. On the other hand, Cu and Fe zeolites show high activity in a low-temperature window and good hydrothermal resistance [11,13,14]. Both copper ions (Cu 2+ and/or Cu + ) and iron ions (Fe 3+ ) play an important role of active sites in the reaction of NH 3 -SCR.…”
Section: Introductionmentioning
confidence: 99%
“…However, the main drawback of V 2 O 5 -WO 3 (MoO 3 )/TiO 2 is a narrow operating temperature window (300-400 • C), sublimation of vanadium species at high temperatures, and high oxidation of SO 2 to SO 3 leading to a decrease of NOx conversion at 400 • C [10]. On the other hand, Cu and Fe zeolites show high activity in a low-temperature window and good hydrothermal resistance [11,13,14]. Both copper ions (Cu 2+ and/or Cu + ) and iron ions (Fe 3+ ) play an important role of active sites in the reaction of NH 3 -SCR.…”
Section: Introductionmentioning
confidence: 99%
“…According to several studies, involving these methods resulted in the stability of Fe containing beta zeolites for NH 3 -SCR. Góra-Marek et al suggested that Fe-BEA synthesized by the ion-exchange method showed high catalytic activity in NH 3 -SCR reaction, which was also supported by Frey et al, while Li et al proposed Fe-BEA prepared by the impregnation method was the most efficient technology . These differences might be attributed to the different proportion of Fe 3+ species located in zeolite matrix based on the different synthesis methods.…”
Section: Introductionmentioning
confidence: 88%
“…In this study a Fe-ZSM-5 catalyst with a Fe loading of 1.5 wt.% and a Cu-SSZ-13 catalyst with a Cu loading of 1.7 wt.% were prepared and coated on honeycombs prior to the testing procedures. Fe-ZSM-5 was synthesized by ion exchange of a commercially purchased NH 4 -ZSM-5 (Si/Al = 12, MFI framework type), analogous to the study of Jablonska et al [46]. The obtained ion exchanged zeolite was washed with deionized water and dried at 70 • C in static air.…”
Section: Catalyst Preparationmentioning
confidence: 99%